ANALISIS KELENGKAPAN BERKAS PASIEN RAWAT JALAN TERHADAP EFISIENSI PENGKLAIMAN BPJS DI RSUD KESEHATAN KERJA PROVINSI JAWA BARAT - Ghani Rizqi Hasani; Ai Susi Susanti (Universitas Bina Taruna Gorontalo, 2023)
The aim of this research is to find out the relationship between the availability of outpatient files and the effectiveness of BPJS claims in the RSUD Kesehatan Kerja in West Java Province. The research method used is descriptive with a quantitative approach. Technique of data collection by means of observation, questionnaires, and library study. Total population of objects: as many as 4,017 respondents. The research sample consists of two types of samples: the subject sample and the object sample. Subject sample of two respondents were taken using purposive sampling. While the sample object as many as 98 patients files for street care, especially patients with BPJS. The data analysis techniques used are validity tests, reliability tests, and Chi-Square tests. The results of the study showed that the level of completeness of the BPJS specialty outpatient files was 31.6%, the rate of effectiveness of BPJS claims was 84.6%, and the Chi-Square test resulted in a P-Value of 0,000 < 0.05. So the conclusion of this study is that there is a relationship between the availability of outpatient files and the effectiveness of BPJS claims in the RSUD Kesehatan Kerja Province of West Java.